Positive-word stimuli via a smartphone application have no immediate-term effects on multi-directional reach ability in standing position: a randomized controlled trial - Kenta Azukizawa; Kodai Hirose; Yuta Morigami; Naoki Higashi; Hiroyuki Uchida; Kazuki Hirao (Annals of Medicine)
Objectives The purpose of the study was to examine the immediate-term effect of positive-word stimuli via a smartphone application on the multi-directional reach ability in standing position in young adults.Methods This study was an immediate-term, assessor-blinded, two-arm, parallel-group, randomized controlled trial among young adults recruited from one university in Japan. Participants were randomly assigned to the experimental group or control group using a computer-based random number-generating programme. Participants of the experimental group used an application on iPhone and watched 3-min videos displaying positive-word stimuli. This application repeatedly displayed positive-word stimuli every 5 s. The participants of the control group used an application on iPhone and watched the same videos as in the experimental group. However, a positive-word stimulus did not appear in the videos. The primary outcome was the multi-directional reach test (MDRT) from baseline to immediately after the intervention protocol.Results Among the 62 randomized participants (experimental group, n = 31; control group, n = 31), 62 (100%) completed the MDRT immediately after the intervention protocol. There were no differences in mean group change values in MDRT between the experimental and control groups.Conclusions Among young adults, positive-word stimuli via a smartphone application did not significantly improve multi-directional reach ability in standing position. These findings do not support the superiority of this intervention among young adults. Trial Registration: Clinicaltrials.gov, NCT03546218. Registered 6 June 2018, https://clinicaltrials.gov/ct2/show/NCT03546218KEY MESSAGESIn our study, among young adults, positive-word stimuli via an SPSRS application did not significantly improve the multi-directional reach ability in the standing position.These findings do not support the superiority of this intervention among young adults.